Complications of Decompressive Craniectomy: A Case-Based Review - Kumarasamy, Sivaraman; Garg, Kanwaljeet; Gurjar, Hitesh Kumar; Praneeth, Kokkula; Meena, Rajesh; Doddamani, Ramesh; Kumar, Amandeep; Mishra, Shashwat; Tandon, Vivek; Singh, Pankaj; Agrawal, Deepak (Indian Journal of Neurotrauma, 2023)
Background Decompressive craniectomy (DC) is a frequently performed procedure to treat intracranial hypertension following traumatic brain injury (TBI) and stroke. DC is a salvage procedure that reduces mortality at the expense of severe disability and compromises the quality of life. The procedure is not without serious complications.Methods We describe the complications following DC and its management in a case-based review in this article.Results Complications after DC are classified as early or late complications based on the time of occurrence. Early complication includes hemorrhage, external cerebral herniation, wound complications, CSF leak/fistula, and seizures/epilepsy. Contusion expansion, new contralateral epidural, and subdural hematoma in the immediate postoperative period mandate surgical intervention. It is necessary to repeat non-contrast CT head at 24 hours and 48 hours following DC. Late complication includes subdural hygroma, hydrocephalus, syndrome of the trephined, bone resorption, and falls on the unprotected cranium. An early cranioplasty is an effective strategy to mitigate most of the late complications.Conclusions DC can be associated with a number of complications. One should be aware of the possible complications, and timely intervention is required.
Keywords: complications; cranioplasty; decompressive craniectomy; intracranial hypertension; traumatic brain injury